Mediating Role of Maladaptive Schemas and Schema Modes between Childhood Maltreatment and Pathological Traits in Adults - Shajiah Malik (Journal of Peace, Development and Communication, 2021)
It was aimed at that maladaptive schemas and Schema modes mediate between childhood maltreatment and pathological traits. It was aimed at maladaptive schema are likely to positively predict the Maladaptive schema modes. It was also aimed at maladaptive schema modes are likely to positively predict the pathological traits. It was aimed at maladaptive schemas are likely to mediate between the childhood maltreatment and pathological traits in adults. It was also aimed at schema modes are likely to mediate between schemas and maladaptive personality traits. Survey research design was used. The present study will be based on survey research design. Sample of the present study will be consisted on university students (N = 300). Purposive sampling technique was used to collect the information. The demographics including gender, education, family system and locality etc will be taken into under considered. Participants will be asked to fill the informed consent. Serial Mediation Analysis was conducted using PROCESS 3.0. The findings indicate that maladaptive schemas and positive schema modes mediated between childhood maltreatment and pathological traits. Maladaptive schemas and negative schema modes mediated between childhood maltreatment and pathological traits. The study supported the schema theory which revealed that early childhood neglect and abuse forms early maladaptive schemas which change into schema modes during the course of development and finally manifested in the form of personality pathologies during adulthood. The study has both theoretical as well as applied significance. The study has supported the theory of Young. Keywords: Childhood Maltreatment, Maladaptive Schemas, Schema Modes, Pathological Traits.